PHILOSOPHICAL PROBLEMS OF EDUCATION IN THE RUSSIAN NATURAL SCIENTIFIC THOUGHT - O. G. Arapov; E. A. Arapova; O. A. Volnyakova; D. V. Solodukhin (Российский технологический журнал)
The article is specially devoted to the study of the philosophical understanding of the higher education problem in the context of modern philosophy by Russian scientists. Fundamental principles of higher education development worked out and represented by M. V. Lomonosov, D.I. Mendeleev, V.I. Vernadsky - the greatest naturalists representing Russian science starting from the 18th century up to our times - are considered. Approaches to organizing university education in Russia, to understanding its content and meaning in preparing professional personnel and educating specialist’s character, to forming humanistically oriented creative thinking and to forming stable worldview are shown. The necessity of various spheres and directions of scientific thought is substantiated. The importance of optimal combination of natural-science, special, abstract philosophical knowledge in the education system is shown. It is noted that the success in overcoming many contemporary problems depends on the degree of understanding the importance of strengthening the relation between science and moral and spiritual basis of human and society life. The question of enhancing the role of humanitarian knowledge in the process of forming the research scientist as socially responsible personality is shown to be topical.